Pengaruh Reputasi Bank dan Inovasi Produk terhadap Keputusan Menabung Nasabah Giro IB Hijrah di Bank Muamalat - Kartika, Rika; Rakhman, Faisal (Jurnal Dimamu, 2025)
This study is based on the decline in the number of IB Hijrah current account customers which is suspected to be influenced by the bank's reputation where customer assessments of the services provided by Bank Muamalat are considered less than good, as well as product innovation factors such as the development of digital access that is not yet optimal. This study aims to determine the effect of bank reputation and product innovation on customer decisions at Bank Muamalat KCP Rancaekek. The object of the study is IB Hijrah current account customers, the type of research is associative quantitative, the type of data is primary data, data collection techniques are in the form of observation, interviews, literature studies and questionnaires. The population is IB Hijrah current account customers in 2023 with a sample of 57 people. The results of the study show that bank reputation and product innovation partially influence decisions by 67.3% and 59.1%, while simultaneously they influence by 75%.